2020
DOI: 10.1111/jce.14379
|View full text |Cite
|
Sign up to set email alerts
|

Clinical investigation of the durability of the lesions created by left atrial linear ablation with a cryoballoon

Abstract: Introduction Pulmonary vein isolation (PVI) and linear ablation with a roof line and bottom line on the left atrial (LA) posterior wall (LAPW) can be achieved with a cryoballoon (CB). This study sought to investigate the long‐term durability of these linear lesions. Methods and results Among 290 persistent patients with atrial fibrillation (AF) who had undergone linear ablation with a CB on the roof and bottom line of the LAPW in addition to the PVI, we analyzed those patients who underwent a re‐do AF ablation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 26 publications
(46 reference statements)
0
24
0
Order By: Relevance
“…Several published studies have described use of the cryoballoon for PWI via linear ablation 41,53,54 . Adjunctive RF ablation is commonly required (~1/3 or more of cases) to achieve PWI and the long‐term durability (at the time of clinically indicated repeat ablation) compared to RF based PWI remains uncertain 41,54 .…”
Section: Emerging Approaches To Energy Deliver To Improve Safety and Efficacy Of Pwimentioning
confidence: 99%
“…Several published studies have described use of the cryoballoon for PWI via linear ablation 41,53,54 . Adjunctive RF ablation is commonly required (~1/3 or more of cases) to achieve PWI and the long‐term durability (at the time of clinically indicated repeat ablation) compared to RF based PWI remains uncertain 41,54 .…”
Section: Emerging Approaches To Energy Deliver To Improve Safety and Efficacy Of Pwimentioning
confidence: 99%
“…Cryoablation outside the PVs has been reported for isolation of the LA roof, 10‐12 the superior vena cava and persistent left superior vena cava, 13,14 the LA appendage, 15 and posterior wall 16‐18 as well as for LA substrate modification 19 …”
Section: Discussionmentioning
confidence: 99%
“…Cryoablation outside the PVs has been reported for isolation of the LA roof, [10][11][12] the superior vena cava and persistent left superior vena cava, 13,14 the LA appendage, 15 and posterior wall [16][17][18] as well as for LA substrate modification. 19 In a multicenter nonrandomized study, PVI + posterior wall isolation (PWI) vs standard PVI using CBA (390 patients, persistent AF) achieved significantly more freedom from AF recurrence at 12 months (80% vs 51%; P = .001).…”
Section: Feasibility Of Extrapulmonary Cryoballoon Ablationmentioning
confidence: 99%
“…Cryolesions created using current-generation cryoballoons typically are large, [29][30][31][32] continuous, 31,32 and durable, 4,5,33 which render it an attractive tool for ablation of extra-PV substrates. A study comparing lesion characteristics and clinical outcomes associated with catheter ablation of AF using the hot balloon (SATAKE HotBalloon, Toray Industries, Inc, Tokyo, Japan) vs the current-generation cryoballoon (Arctic Front Advance, Medtronic, Minneapolis, MN) found that lesions created using the latter were significantly larger (38 6 12 cm 2 vs 24 6 8 cm 2 ).…”
Section: Noca Of Extra-pv Structures Rationalementioning
confidence: 99%
“…However, PV occlusion is not an absolute requirement for creating durable cryolesions. 4,5 Based on available data, myocardial cells are rendered electrically dormant (ie, reversible ion channel block) at 120 C to 125 C with irreversible, lethal effects achieved at temperatures of -20 C to -50 C. 6,7 Although PV occlusion likely augments the "magnitude of the freeze," optimal tissue contact and not necessarily PV occlusion, which in itself implies the same, is quintessential for creating durable cryolesions. This notion is further supported by finite element modeling data 8 and clinically corroborated when performing nonocclusive cryoballoon ablation (NOCA) to target large-sized PVs in a segmental approach, as in the case of large, common PV ostia 9 and the left atrial (LA) roof (NOCAROOF) [10][11][12][13] and posterior wall (PW) (NOCALAPW).…”
Section: Introductionmentioning
confidence: 99%